Clinico-pathological features of the intradiaphragmatic bronchogenic cysts: report of a case and review of the literature - SIMONETTI, S.; CANALÍS, E.; MACÍAS, L.; CARRASCO, M.A. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2018)
Bronchogenic cysts represent congenital malformations deriving from an abnormal development of the primitive foregut during embryogenesis. These lesions are rarely found and they are most frequently localized in the mediastinum, or in lung parenchyma. Intramuscular localization is extremely rare, especially within the diaphragm. We report a case of a 54 year old man showing a large lobulated cystic lesion in the left hemidiaphragm. Complete surgery was performed and histological diagnosis of intradiaphragmatic bronchogenic cyst was made during surgery and confirmed after a total section analysis. Moreover we reviewed the other cases published in the English literature, including clinical, surgical and pathological data.